Core-shell solid electrolyte material, preparation method thereof and all-solid-state lithium metal battery
By forming a fluoride coating on the surface of the chloride solid electrolyte in situ, the instability problem of chloride electrolyte to air and metal lithium is solved, and higher battery cycle stability and safety are achieved, while reducing production costs.
Patent Information
- Application Number
- CN202411764888.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-12-03
AI Technical Summary
The existing chloride solid electrolyte hydrolyzed in the air to produce toxic gases, and the interface stability with metal lithium is poor, resulting in battery cycle stability and safety hazards.
The fluoride cladding layer is formed by fluorinating in situ on the surface of the chloride solid electrolyte to form a core-shell structure, avoiding contact with water vapor and suppressing side reactions with metal lithium.
It improves the air stability and metal lithium compatibility of chloride electrolytes, enhances the cycle stability and safety of the battery, and reduces production costs.
Smart Images

Figure CN119581649A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of solid electrolytes, and in particular relates to a fluoride-coated core-shell chloride solid electrolyte and a preparation method thereof, and an all-solid-state lithium metal battery. Background Art
[0002] As a new generation of energy storage technology, all-solid-state lithium metal batteries have attracted widespread attention due to their high safety, high energy density and long cycle life. Compared with traditional liquid lithium-ion batteries, all-solid-state lithium metal batteries use solid electrolyte materials, which can not only effectively solve the safety hazards such as flammable and explosive organic electrolytes, but also significantly improve the energy density through the use of lithium metal negative electrodes. Therefore, all-solid-state lithium metal batteries are regarded as one of the core technologies to promote the development of next-generation electric vehicles, smart grids and portable electronic devices.
[0003] In the development of all-solid-state lithium metal batteries, the selection of solid electrolyte materials is crucial. At present, chloride solid electrolytes have become a hot topic of research due to their high ionic conductivity and high voltage stability. However, existing chloride solid electrolytes still face some technical bottlenecks in practical applications, especially in terms of air stability and compatibility with metallic lithium. First, chloride solid electrolytes are extremely sensitive to moisture in the air. When exposed to air, they will undergo hydrolysis reactions, resulting in the production of toxic HCl gas and a significant decrease in ionic conductivity, which seriously limits their large-scale application. In addition, the interface stability between chloride electrolytes and metallic lithium is poor, and interfacial reactions will spontaneously occur to generate ion-insulating interfacial byproducts, thereby reducing the cycle stability of the battery. In addition, chloride electrolytes may also induce lithium dendrite growth due to side reactions during the charge and discharge cycle, further deteriorating battery performance and possibly causing safety hazards. Therefore, the development of chloride solid electrolyte materials that are stable to metallic lithium and humid air is of great significance for promoting the practical application of all-solid-state lithium metal batteries.
[0004] Patent document 1 (CN117996164A) discloses a composite solid electrolyte, which includes a halide solid electrolyte and a coating layer coated on the surface of the halide solid electrolyte, wherein the coating layer includes a first lithium salt, and the first lithium salt includes at least one of lithium difluorophosphate (LiPO2F2), lithium difluorooxalate borate (LiDFOB), lithium dioxalate borate (LiBOB), and lithium dioxalate difluorophosphate (LiODFP). In Patent Document 1, a layer of lithium salt is coated on the surface of the halide solid electrolyte, and during charging, the halide solid electrolyte is in-situ decomposed to form a material with high oxidation stability and fast lithium conduction, such as LiF, LiBO2, Li3PO4, etc., thereby isolating the electron path.
[0005] Although Patent Document 1 isolates the electron path by forming a coating layer on the surface of the halide solid electrolyte, it is necessary to decompose the lithium salt to form a fast lithium-conducting material during charging, which is likely to result in insufficient decomposition of the lithium salt and uneven coating. In addition, in actual industrial production, cost is a very important factor to be considered. The lithium salts used in Patent Document 1 are all relatively expensive, resulting in a significant increase in cost in practical applications. Summary of the invention
[0006] Problem that the invention aims to solve
[0007] In view of the problems existing in the prior art, it is necessary to provide a chloride solid electrolyte which can not only avoid the contact between the chloride electrolyte and water vapor, inhibit the side reaction between the chloride electrolyte and metallic lithium and the growth of lithium dendrites, but also has a low cost.
[0008] Solutions for solving problems
[0009] In order to achieve the above object, the technical solution adopted by the present invention is: using a chloride solid electrolyte as the core, and coating the surface with fluoride to form a shell structure by in-situ fluorination. Under the protection of the fluoride shell, the chloride electrolyte can not only avoid the contact between the chloride electrolyte core and water vapor, but also inhibit the side reaction between the chloride electrolyte core and lithium metal and the growth of lithium dendrites, thereby achieving the excellent stability of the chloride electrolyte to humid air and metallic lithium.
[0010] Specifically, the present invention provides a core-shell solid electrolyte material, which uses a chloride solid electrolyte as a core and forms a fluoride coating layer as a shell on the surface of the chloride solid electrolyte by in-situ fluorination.
[0011] The chemical formula of the chloride solid electrolyte is Li a M 6-a Cl6, where M is In 3+ , Y 3+ 、Al 3+ , Fe 3+ 、Lu 3+ , Tb 3+ 、Ti 3+ Sc 3+ , Er 3+ 、Ho 3+ , Yb 3+ 、Dy 3+ 、Tm 3+ 、Zr 4+ One or more elements in , 1≤a≤3.
[0012] According to the core-shell solid electrolyte material described above, the fluoride is one or more of LiF, NaF, KF, CaF2, MgF2, MnF2, InF3, YF3, AlF3, FeF3, LuF3, TbF3, TiF3, ScF3, ErF3, HoF3, YbF3, DyF3, TmF3, and ZrF4.
[0013] According to the core-shell solid electrolyte material described above, the room temperature ionic conductivity of the core-shell solid electrolyte material is ≥2.0×10 -4 S / cm; and / or
[0014] When the core-shell solid electrolyte material is exposed to air with a relative humidity of 20-50% for 2-24 hours, the room temperature ion conductivity retention rate thereof is ≥40%.
[0015] According to the core-shell solid electrolyte material described above, the thickness of the fluoride coating layer is 1-10 nm.
[0016] According to the core-shell solid electrolyte material described above, the particle size of the chloride solid electrolyte is 1-30 μm.
[0017] The present invention also provides a method for preparing the core-shell solid electrolyte material described above, which comprises the following steps:
[0018] A fluoriding agent is mixed with a chloride solid electrolyte and subjected to heat treatment, thereby obtaining a core-shell solid electrolyte material with a fluoride coated on the surface.
[0019] According to the preparation method described above, the fluorinating agent is one or more of NH4F, LiHF2, LiNH4HF2, NaHF2, KHF2, MnHF2, NaNH4HF2, CaHF2, and MgHF2.
[0020] According to the preparation method described above, the mass ratio of the fluorinating agent to the chloride solid electrolyte is 1:200 to 1:2, preferably 1:50 to 1:5.
[0021] According to the preparation method described above, the heat treatment is carried out under an argon atmosphere; the heating rate is 1-5°C / min, the heat treatment temperature is 100-1000°C, and the heat treatment time is 1-48h.
[0022] The present invention further provides an all-solid-state lithium metal battery, which comprises a positive electrode, a negative electrode and an electrolyte layer, wherein at least one of the positive electrode, the electrolyte layer and the negative electrode contains the core-shell solid electrolyte material described above or the core-shell solid electrolyte material obtained by the preparation method described above.
[0023] Effects of the Invention
[0024] The above technical solution of the present invention has the following beneficial effects:
[0025] (1) The core-shell solid electrolyte material of the present invention forms a fluoride coating layer on the surface of the chloride electrolyte core by in-situ fluorination, so the interface stability between the fluoride shell and the chloride electrolyte core is good, which can improve the battery capacity and capacity retention rate.
[0026] (2) In the core-shell solid electrolyte material of the present invention, due to the presence of the fluoride shell, the contact between the chloride electrolyte core and water vapor can be avoided and the side reaction between the chloride electrolyte core and metallic lithium and the growth of lithium dendrites can be inhibited, thereby achieving excellent stability of the chloride electrolyte to humid air and metallic lithium; the core-shell solid electrolyte material of the present invention has a high conductivity retention rate in humid air;
[0027] (3) The present invention utilizes the strong corrosiveness of HF, a gas phase decomposition product of a relatively low-cost fluorinating agent, to in-situ fluorinate the surface of the chloride electrolyte, thereby obtaining a core-shell solid electrolyte material of a fluoride-coated chloride solid electrolyte, which has the advantages of simple operation method, low cost, and easy large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 X-ray diffraction patterns of the LiF-ZrF4 coated core-shell LiF-ZrF4@Li2ZrCl6 chloride electrolyte of Example 1 of the present invention and the Li2ZrCl6 chloride electrolyte of Comparative Example 1.
[0029] Figure 2 This is a high-resolution transmission electron microscopy of the LiF-ZrF4-coated core-shell LiF-ZrF4@Li2ZrCl6 chloride electrolyte of Example 1 of the present invention.
[0030] Figure 3 This is a cycle diagram of a lithium symmetric battery assembled based on the LiF-ZrF4 coated core-shell LiF-ZrF4@Li2ZrCl6 chloride electrolyte of Example 1 of the present invention and the Li2ZrCl6 chloride electrolyte of Comparative Example 1.
[0031] Figure 4 This is a charge and discharge cycle diagram of an all-solid-state lithium metal battery assembled based on the LiF-ZrF4-coated core-shell LiF-ZrF4@Li2ZrCl6 chloride electrolyte of Example 1 of the present invention and the Li2ZrCl6 chloride electrolyte of Comparative Example 1. DETAILED DESCRIPTION
[0032] In order to better illustrate the present invention, numerous specific details are provided in the following specific embodiments. It should be understood by those skilled in the art that the present invention can be implemented without certain specific details. In other examples, methods, means, equipment and steps well known to those skilled in the art are not described in detail in order to highlight the subject matter of the present invention.
[0033] Unless otherwise stated, the units used in this specification are all international standard units, and the numerical values and numerical ranges appearing in the present invention should be understood to include the inevitable systematic errors in industrial production.
[0034] In this specification, the word "may" means both performing a certain process and not performing a certain process.
[0035] In this specification, the references to "some specific / preferred embodiments", "other specific / preferred embodiments", "embodiments", etc., mean that the specific elements (e.g., features, structures, properties and / or characteristics) described in connection with the embodiments are included in at least one embodiment described herein, and may or may not exist in other embodiments. In addition, it should be understood that the elements may be combined in various embodiments in any suitable manner.
[0036] In this specification, the numerical range expressed using "a numerical value A to a numerical value B" means a range including the endpoints numerical values A and B.
[0037] In this specification, unless otherwise specified, the word "multiple" in "multiple", "multiple", "plurality", etc. means a numerical value of 2 or more.
[0038] In the present specification, the term “substantially”, “substantially” or “essentially” means that the error is less than 5%, or less than 3%, or less than 1% compared with a relevant perfect standard or theoretical standard.
[0039] In this specification, unless otherwise specified, "%" means mass percentage.
[0040] In this specification, the word "may" means both performing a certain process and not performing a certain process.
[0041] In the present specification, "optional" or "optionally" means that the event or situation described below may or may not occur, and the description includes cases where the event occurs and cases where it does not occur.
[0042] In this specification, if "room temperature" or "normal temperature" appears, the temperature may generally be 25±5°C.
[0043] First aspect
[0044] The first aspect of the present invention provides a core-shell solid electrolyte material. The core-shell solid electrolyte material of the present invention has a chloride solid electrolyte as a core and forms a fluoride coating layer as a shell on the surface of the chloride solid electrolyte by in-situ fluorination.
[0045] In the present invention, the chemical formula of the chloride solid electrolyte is Li a M 6-a Cl6, where M is In 3+ , Y 3+ 、Al 3+ , Fe 3 + 、Lu 3+ , Tb 3+ 、Ti 3+ Sc 3+ , Er 3+ 、Ho 3+ , Yb 3+ 、Dy 3+ 、Tm 3+ 、Zr 4+ One or more elements in , 1≤a≤3. In some specific embodiments, M may be preferably Zr 4+ 、In 3+ or Y 3+ , a is 2 or 3.
[0046] In some specific embodiments, the fluoride may be one or more of LiF, NaF, KF, CaF2, MgF2, MnF2, InF3, YF3, AlF3, FeF3, LuF3, TbF3, TiF3, ScF3, ErF3, HoF3, YbF3, DyF3, TmF3, and ZrF4. In some embodiments, the fluoride may be a combination of LiF and one or more selected from NaF, KF, CaF2, MgF2, MnF2, InF3, YF3, AlF3, FeF3, LuF3, TbF3, TiF3, ScF3, ErF3, HoF3, YbF3, DyF3, TmF3, and ZrF4.
[0047] The room temperature ionic conductivity of the core-shell solid electrolyte material of the present invention is ≥2.0×10 -4 S / cm, for example, can be 2.0×10 -4 S / cm, 2.5×10 -4 S / cm, 3.0×10 -4 S / cm, 5.0×10 -4 S / cm, 8.0×10 -4 S / cm, 1.0×10-3 S / cm, 3.0×10 -3 S / cm, etc.
[0048] The core-shell solid electrolyte material is exposed to air at a relative humidity of 20-50% for 2-24 hours, and its room temperature ionic conductivity retention rate is ≥40%, for example, 50%, 60%, 70%, 80%, etc.
[0049] In the core-shell solid electrolyte material of the present invention, the thickness of the fluoride coating layer may be 1-10 nm, for example, 3 nm, 5 nm, 8 nm, 10 nm, etc.
[0050] In the core-shell solid electrolyte material of the present invention, the particle size of the chloride solid electrolyte may be 1-30 μm, for example, 1 μm, 3 μm, 5 μm, 8 μm, 10 μm, 12 μm, 15 μm, 20 μm, 25 μm, 30 μm, etc.
[0051] Second aspect
[0052] The second aspect of the present invention provides a method for preparing the core-shell solid electrolyte material described in the first aspect.
[0053] The preparation method of the invention comprises the following steps: mixing a fluoriding agent with a chloride solid electrolyte and performing heat treatment, and obtaining a core-shell solid electrolyte material with a fluoride coated on the surface after cooling.
[0054] When the mixture of the fluorinating agent and the chloride solid electrolyte is heat-treated, the fluorinating agent is thermally decomposed to produce highly corrosive HF gas, and the HF gas fluorinates the surface of the chloride solid electrolyte, and an in-situ fluorination reaction occurs, thereby forming a fluoride coating on the surface of the chloride solid electrolyte. The core-shell structure formed by in-situ fluorination has good interface stability between the fluoride shell and the chloride electrolyte core. The fluoride coating acts as a shell to protect the chloride solid electrolyte core, avoid contact between the chloride electrolyte core and water vapor, and prevent the chloride solid electrolyte from reacting with metallic lithium.
[0055] The chloride solid electrolyte in this aspect is the same as that in the first aspect above, and will not be described in detail here.
[0056] The fluorinating agent used in the present invention may be one or more of NH4F, LiHF2, LiNH4HF2, NaHF2, KHF2, MnHF2, NaNH4HF2, CaHF2, and MgHF2. Among them, NH4F is preferably used from the perspective of cost.
[0057] In the present invention, the mass ratio of the fluorinating agent to the chloride solid electrolyte may be 1:200 to 1:2, for example, 1:150, 1:120, 1:100, 1:80, 1:50, 1:30, 1:10, 1:8, 1:5, 1:3, etc.
[0058] In the present invention, after the fluorinating agent and the chloride solid electrolyte are mixed, they can be ground by a mortar, etc. to mix them uniformly. After the fluorinating agent and the chloride solid electrolyte are mixed uniformly, they are heat treated and cooled to obtain a core-shell solid electrolyte material with a core of the chloride solid electrolyte and an outer shell of the fluoride.
[0059] The heat treatment may be performed under an argon atmosphere. The heating rate may be 1 to 5°C / min. The heat treatment temperature may be 100 to 1000°C, for example, 150°C, 200°C, 250°C, 300°C, 500°C, 700°C, 900°C, etc. The heat treatment time may be 1 to 48h, for example, 1.5h, 2h, 5h, 10h, 15h, 20h, 30h, 40h, etc.
[0060] In the present invention, there is no particular limitation on the preparation method of the chloride solid electrolyte, and the solid electrolyte can be prepared using conventional preparation methods in the art, such as solid ball milling method.
[0061] When the chloride solid electrolyte is prepared by the solid ball milling method, LiCl and the chloride of element M can be uniformly mixed according to the stoichiometric ratio under the protection of argon gas, and then the obtained mixture is ball milled at high speed for a period of time, for example, 15 to 30 hours, to obtain the chloride solid electrolyte.
[0062] The third aspect
[0063] The third aspect of the present invention further provides an all-solid-state lithium battery, which comprises a positive electrode, a negative electrode and an electrolyte layer, wherein at least one of the positive electrode, the electrolyte layer and the negative electrode contains the core-shell solid electrolyte material described above or the core-shell solid electrolyte material obtained by the preparation method described above.
[0064] In the present invention, there is no particular limitation on other materials used for the positive electrode, the negative electrode and the electrolyte layer, and materials known in the art can be used.
[0065] Example
[0066] The embodiments of the present invention will be described in detail below in conjunction with the examples, but those skilled in the art will appreciate that the following examples are only used to illustrate the present invention and should not be considered to limit the scope of the present invention. If no specific conditions are specified in the examples, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be obtained commercially.
[0067] Example 1: Preparation of LiF-ZrF4@Li2ZrCl6 chloride solid electrolyte material
[0068] 1) Under the protection of argon, LiCl and ZrCl4 raw materials were mixed uniformly according to the stoichiometric ratio, and then the obtained mixture was ball-milled at 800 rpm for 20 h to obtain Li2ZrCl6 chloride solid electrolyte.
[0069] 2) weighing the fluorinating agent NH4F and the Li2ZrCl6 chloride solid electrolyte in a mass ratio of 1:10, and mixing them evenly in a mortar to obtain a precursor;
[0070] 3) The obtained precursor is heated from room temperature to 200°C at a heating rate of 1°C / min under an argon atmosphere and kept warm for 2 hours, wherein the highly corrosive HF gas produced by the thermal decomposition of NH4F will fluorinate the surface of Li2ZrCl6 to obtain a core-shell LiF-ZrF4@Li2ZrCl6 coated with LiF and ZrF4.
[0071] Figure 1 and Figure 2 The X-ray diffraction patterns and high-resolution transmission electron microscopy images of the LiF-ZrF4@Li2ZrCl6 chloride electrolyte coated with LiF and ZrF4 prepared by the present invention are shown respectively. Figure 1 It can be seen from the characteristic peaks that in addition to the original peaks of Li2ZrCl6, additional diffraction peaks were observed in Example 1 that can be indexed with the standard peaks of LiF (PDF#45-1460) and ZrF4 (PDF#46-1201), indicating that the coating layers of LiF and ZrF4 were successfully formed during the fluorination process. Figure 2 From the high-resolution transmission electron microscopy photograph shown, it can be seen that the thickness of the coating layer is about 5 nm.
[0072] Based on the LiF-ZrF4@Li2ZrCl6 prepared in Example 1, a stainless steel symmetric battery was assembled to test the change in ionic conductivity before and after exposure to air. In a glove box filled with argon, 100 mg of LiF-ZrF4@Li2ZrCl6 electrolyte was taken before and after exposure to air, placed in a mold with a diameter of 10 mm, and pressed into an electrolyte sheet under a pressure of 300 MPa. Subsequently, the stainless steel discs were placed on both sides to assemble a symmetrical battery. The mold pressure was maintained at 100 MPa, and impedance testing was performed using an electrochemical workstation (the same method was used in the following examples). The ionic conductivity of the core-shell LiF-ZrF4@Li2ZrCl6 chloride solid electrolyte before exposure to humid air was measured to be 2.15×10 -4S / cm, and after exposure to humid air with a relative humidity of 25% for 2 h, the ionic conductivity dropped to 1.47×10 -4 S / cm, and the ionic conductivity retention rate was 68.37%.
[0073] Example 2: Preparation of LiF-InF3@Li3InCl6 chloride solid electrolyte material
[0074] 1) Under the protection of argon, LiCl and InCl3 raw materials were mixed uniformly according to the stoichiometric ratio, and then the mixture was high-speed ball milled at 800 rpm for 20 h. The ball-milled mixed sample was heated from room temperature to 260°C at a heating rate of 1°C / min, kept warm for 5 h, and cooled to obtain Li3InCl6 chloride solid electrolyte.
[0075] 2) Under the protection of argon atmosphere, weigh the fluorinating agent NH4F and Li3InCl6 chloride solid electrolyte in a mass ratio of 1:10, and mix them evenly in a mortar to obtain a precursor;
[0076] 3) The obtained precursor is heated from room temperature to 200°C at a heating rate of 1°C / min under an argon atmosphere and kept warm for 2 hours, wherein the highly corrosive HF gas produced by the thermal decomposition of NH4F will fluorinate the surface of Li3InCl6 to obtain a core-shell LiF-InF3@Li3InCl6 coated with LiF and InF3.
[0077] The ionic conductivity of the core-shell LiF-InF3@Li3InCl6 chloride solid electrolyte before exposure to humid air was measured to be 3.15×10 -3 S / cm. After exposure to humid air with a relative humidity of 25% for 2 h, the ionic conductivity dropped to 2.36×10 - 4 S / cm, and the ionic conductivity retention rate was 74.92%.
[0078] Example 3: Preparation of LiF-YF3@Li3YCl6 chloride solid electrolyte material
[0079] 1) Under the protection of argon, LiCl and YCl3 raw materials were mixed uniformly according to the stoichiometric ratio, and then the mixture was high-speed ball milled at 800 rpm for 20 h. The ball-milled mixed sample was heated from room temperature to 260°C at a heating rate of 1°C / min, kept warm for 5 h, and cooled to obtain Li3YCl6 chloride solid electrolyte.
[0080] 2) Under the protection of an argon atmosphere, weigh the fluorinating agent NH4F and the Li3YCl6 chloride solid electrolyte in a mass ratio of 1:10, and mix them evenly in a mortar to obtain a precursor;
[0081] 3) The obtained precursor is heated from room temperature to 200°C at a heating rate of 1°C / min under an argon atmosphere and kept warm for 2 hours, wherein the highly corrosive HF gas produced by the thermal decomposition of NH4F will fluorinate the surface of Li3YCl6 to obtain a core-shell LiF-YF3@Li3YCl6 coated with LiF and YF3.
[0082] The ionic conductivity of the core-shell LiF-YF3@Li3YCl6 chloride solid electrolyte before exposure to humid air was measured to be 2.68×10 -3 S / cm. After exposure to humid air with a relative humidity of 25% for 2 h, the ionic conductivity dropped to 1.76×10 -4 S / cm, and the ionic conductivity retention rate was 65.67%.
[0083] Comparative Example 1: Preparation of Li2ZrCl6 chloride solid electrolyte material
[0084] Under the protection of argon, LiCl and ZrCl4 raw materials were mixed evenly according to the stoichiometric ratio, and then the obtained mixture was ball-milled at 800 rpm for 20 h to obtain Li2ZrCl6 chloride solid electrolyte.
[0085] The ionic conductivity of Li2ZrCl6 chloride solid electrolyte before exposure to humid air was measured to be 5.62×10 -4 S / cm. After exposure to humid air with a relative humidity of 25% for 2 h, the ionic conductivity dropped to 2.26×10 -6 S / cm, and the ionic conductivity retention rate is only 0.04%.
[0086] Lithium Metal Stability Test
[0087] A lithium symmetrical battery was assembled based on the LiF-ZrF4@Li2ZrCl6 prepared in Example 1 and the Li2ZrCl6 chloride solid electrolyte material prepared in Comparative Example 1. In a glove box filled with argon, 100 mg of LiF-ZrF4@Li2ZrCl6 and Li2ZrCl6 electrolyte were taken respectively, placed in a mold with a diameter of 10 mm, and pressed into an electrolyte sheet at a pressure of 300 MPa. Subsequently, lithium sheets with a diameter of 9 mm were placed on both sides of the electrolyte sheet to assemble a lithium symmetrical battery. The mold pressure was maintained at 100 MPa, and a long cycle test was carried out by a blue electric device at a current density and surface capacity of 0.1 mA / cm and 0.1 mAh / cm, respectively.
[0088] Figure 3This is a comparison chart of the long cycle test of lithium symmetric batteries assembled based on LiF-ZrF4@Li2ZrCl6 prepared in Example 1 and Li2ZrCl6 chloride solid electrolyte materials prepared in Comparative Example 1 at current density and surface capacity of 0.1 mA / cm and 0.1 mAh / cm respectively. Figure 3 (a) It can be found that the overpotential of the lithium symmetric battery assembled in Comparative Example 1 increases with the increase of the number of cycles, and reaches a cut-off voltage of 5V after 156h. Figure 3 (b) It can be found that the lithium symmetric battery assembled in Example 1 can be stably cycled for more than 800 hours. The test results show that the fluoride-coated core-shell chloride electrolyte obtained based on the present invention has excellent stability to metallic lithium.
[0089] Application of solid electrolytes in all-solid-state metal batteries
[0090] The LiCoO2 positive electrode, the metallic lithium negative electrode and the LiF-ZrF4@Li2ZrCl6 prepared in Example 1 or the Li2ZrCl6 chloride solid electrolyte material prepared in Comparative Example 1 are assembled into an all-solid-state lithium metal battery, and a constant current charge and discharge test is carried out in the voltage range of 2.8 to 4.3 V using a blue power device, and the charge and discharge rate is 0.2C.
[0091] Figure 4 The cycle curve of the all-solid-state lithium battery assembled based on the LiF-ZrF4@Li2ZrCl6 prepared in Example 1 or the Li2ZrCl6 chloride solid electrolyte material prepared in Comparative Example 1 at 0.2C. As can be seen, the discharge capacity of the all-solid-state lithium battery assembled based on Comparative Example 1 is 102.8mAh / g in the first cycle, but it drops to 22.3mAh / g after only 6 cycles, and the capacity retention rate after 6 cycles is only 21.7%. In contrast, the all-solid-state lithium battery assembled based on Example 1 has an initial capacity of 128.6mAh / g, a capacity of 90.8mAh / g after 100 cycles, and a capacity retention rate of 71% after 100 cycles. The test results show that the all-solid-state battery prepared by the fluoride-coated core-shell chloride electrolyte has better cycle stability.
[0092] The embodiments of the present invention have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and changes will be apparent to those skilled in the art without departing from the scope and spirit of the described embodiments.
Claims
1. A core-shell solid electrolyte material, characterized in that: The invention uses a chloride solid electrolyte as the core, and forms a fluoride coating layer as the shell on the surface of the chloride solid electrolyte through in-situ fluorination. The chemical formula of the chloride solid electrolyte is Li a M 6-a Cl6, where M is In 3+ , Y 3+ 、Al 3+ , Fe 3+ 、Lu 3+ , Tb 3+ 、Ti 3+ Sc 3+ , Er 3+ 、Ho 3+ , Yb 3+ 、Dy 3+ 、Tm 3+ 、Zr 4+ One or more elements in , 1≤a≤3.
2. The core-shell solid electrolyte material according to claim 1, characterized in that The fluoride is one or more of LiF, NaF, KF, CaF2, MgF2, MnF2, InF3, YF3, AlF3, FeF3, LuF3, TbF3, TiF3, ScF3, ErF3, HoF3, YbF3, DyF3, TmF3, and ZrF4.
3. The core-shell solid electrolyte material according to claim 1 or 2, characterized in that: The room temperature ionic conductivity of the core-shell solid electrolyte material is ≥2.0×10 -4 S / cm; and / or When the core-shell solid electrolyte material is exposed to air with a relative humidity of 20-50% for 2-24 hours, the room temperature ion conductivity retention rate thereof is ≥40%.
4. The core-shell solid electrolyte material according to any one of claims 1 to 3, characterized in that The thickness of the fluoride coating layer is 1-10 nm.
5. The core-shell solid electrolyte material according to any one of claims 1 to 4, characterized in that: The particle size of the chloride solid electrolyte is 1-30 μm.
6. A method for preparing the core-shell solid electrolyte material according to any one of claims 1 to 5, characterized in that: The following steps are involved: A fluoriding agent is mixed with a chloride solid electrolyte and subjected to heat treatment, thereby obtaining a core-shell solid electrolyte material with a fluoride coated on the surface.
7. The preparation method according to claim 6, characterized in that: The fluorinating agent is one or more of NH4F, LiHF2, LiNH4HF2, NaHF2, KHF2, MnHF2, NaNH4HF2, CaHF2, and MgHF2.
8. The preparation method according to claim 6 or 7, characterized in that: The mass ratio of the fluorinating agent to the chloride solid electrolyte is 1:200 to 1:2, preferably 1:50 to 1:
5.
9. The preparation method according to any one of claims 6 to 8, characterized in that: The heat treatment is carried out in an argon atmosphere; the heating rate is 1-5°C / min, the heat treatment temperature is 100-1000°C, and the heat treatment time is 1-48h.
10. An all-solid-state lithium metal battery, characterized in that: It comprises a positive electrode, a negative electrode and an electrolyte layer, wherein at least one of the positive electrode, the electrolyte layer and the negative electrode contains the core-shell solid electrolyte material according to any one of claims 1 to 5 or the core-shell solid electrolyte material obtained by the preparation method according to any one of claims 6 to 9.
Citation Information
Patent Citations
Composite solid electrolyte, preparation method thereof and lithium ion battery
CN117996164A
Solid electrolyte composite material with core-shell structure as well as preparation method and application of solid electrolyte composite material
CN115000502A
Halide solid electrolyte powder material, preparation method thereof and solid-state battery
CN115332616A
Fluorine-containing solid polymer electrolyte material and preparation method and application thereof
CN116799298A
Composite solid electrolyte, preparation method thereof and lithium ion battery
CN117747929A
Cited By
Preparation method of solid electrolyte of lithium battery
CN120221771A